Development of Interactive Videos on Hydrocarbon Material to Train Students' Visual Intelligence - Fauziah Sya’bani Oktabrina; Kusumawati Dwiningsih; Maharani Agustina Arivi (Jurnal Pendidikan Sains Indonesia, 2026)
Learning chemistry about hydrocarbon compounds presents significant challenges for teachers, as many of the concepts taught are abstract, involve many ideas that need to be memorized, and are imaginative. The problem faced by students is the limitation in visualizing the form of hydrocarbon compounds, so it is necessary to develop media to train their visual intelligence. This was revealed from interviews with chemistry teachers at high schools in Surabaya and a pre research survey of eleventh grade students, which showed that visual intelligence related to hydrocarbons is still relatively low, with an average ability of only 44 percent. One media that is suitable for the characteristics of learning in the 21st century is interactive video. Based on the things that have been explained, this research developed interactive video media that integrates visual intelligence training on hydrocarbon compounds, with the aim of describing the feasibility of the developed media. The research and development (R&D) method used was a 4D model, but was limited to 3 development stages. A limited trial was conducted involving 20 eleventh grade students. The average visual intelligence score increased from 48 in the pretest to 88 in the posttest. The Wilcoxon Signed Rank test showed a significance value of 0.000 with an effect size (r = 0.89), indicating a significant improvement. Therefore, the developed interactive video media, which combines molecular visualization and provides direct feedback, can effectively support the visual process in understanding abstract chemical concepts.